Artificial Intelligence in Education: Awareness, Readiness and Practice of Using Artificial Intelligence Technologies in Professional Activities by University Faculty - P. V. Sysoyev (Высшее образование в России)
Daily artificial intelligence (AI) technologies are being implemented deeper and deeper in all spheres of human life, including education. At the same time, the degree of integration of AI tools into the pedagogical process largely depends on the awareness, readiness and practice of using the entire AI arsenal by teachers in their professional activities. The purpose of this study is to identify the awareness of university faculty in the use of AI tools in teaching activities, as well as to determine the degree of their readiness and practice of using AI technology in the educational process. The survey participants were 426 teachers from 18 universities of the Russian Federation. The results of the survey showed that the integration of AI tools in education is currently at an early stage. In general, university faculty lack a systematic understanding of the organizational, teaching and learning potential of AI tools. Many educators have segmental knowledge, related to a greater extent directly to their professional activities in teaching specific disciplines, and are not able to create a complete picture of the possibilities of AI in education. At the same time, most university professors express a neutral attitude or readiness to use AI tools in teaching activities. The experience of practical application of AI tools in the pedagogical process is limited to a few cases of using specific technologies in teaching specific aspects of disciplines.